Manejo de siratro com glyphosate e carfentrazone-ethyl em diferentesintensidades luminosas - Gustavo Amaral Costa (2015)
The emergence of weeds tolerant to glyphosate as siratro (Macroptiliumatropurpureum) and the fact that the control recommendations do not take into account the different light intensities in which plants are allocated, has become constant problem in agriculture.The use of herbicides with different mechanisms of action or even a combination of products is fundamental to draw the appropriate management of species tolerant to herbicides in varied environments.The objective of this study was to evaluate the relationship between light availability and the application of glyphosate and carfentrazoneethyl, individually or in combination, on the physiological, anatomical aspects and control siratro plants. The trial was conducted in pots in a randomized block design with 5 repetitions.The treatments were arranged in a 3x4 factorial design, with different brightness (0 or full sun, 50 and 70% shade) and two combined or not herbicides, arranged in: 40 g ha-1 of carfentrazoneethyl, 1440 g ha-1 of glyphosate, 1080+30 g ha-1 of glyphosate + carfentrazone-ethyl and control.They were evaluated the percentage control of the plants, anatomical aspects through light and scanning microscopy, physiological characteristics after herbicide application, in addition to quantified the epicuticular wax and biomass. The applications of glyphosate and carfentrazone-ethyl isolated did not result in satisfactory effect in controlling siratro plants kept in full sun.However, the combination of carfentrazone-ethyl and glyphosate was favorable for siratro control in all environments, confirming additive effect of the mixture. Siratro plants grown in full sun showed higher density of trichomes in leaves and larger amount of waxes, which may be related to greater tolerance of these individuals when compared to plants grown under shade.The shading imposed the cultivation of this plant decreased the leaf blade thickness and deposition of wax compared to plants grown in full sun. Herbicides when in contact with the trichomes promote the loss of turgor of this structure. Isolated applications of carfentrazone-ethyl in the shadow caused the rupture of the cuticle. The shading promoted reductions in stomatal conductance and efficiency in water use.The combination of glyphosate and carfentrazone-ethyl promoted drastic reduction in the stomatal conductance, water use and internal carbon leaves efficiency. The interaction of the shading with herbicides reduces the photosynthetic rate and efficiency in water use. The dry biomass of the aerial part suffered cuts from the interaction between light intensities and doses of herbicides.However, in isolated applications of carfentrazone-ethyl biomass remained with values close to witness in full sun. The phenotypic plasticity in the leaf morphoanatomy restriction imposed by the luminous favored the absorption and translocation of the herbicide.It can be inferred that the reduction in dry matter accumulation by siratro plants in the shade justifies by the lower photosynthetic efficiency and other physiological parameters as well as the enhancement of herbicide glyphosate effect, carfentrazone-ethyl and glyphosate + carfentrazone-ethyl under light restriction.